THE EFFECT OF PRICE, STORE AMBIENCE AND SERVICE QUALITY ON CUSTOMER LOYALTY AT FRITTO CHICHEN IN MEDAN CITY - Delina Hati Maduwu; Tika Nirmala Sari (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to determine and analyze the effect of price, store ambience, and service quality on customer loyalty at Fritto Chicken Medan City. This study uses a quantitative method with a causal associative approach. The population in this study were Fritto Chicken Medan City customers with a sample of 100 respondents obtained using quota sampling and purposive sampling techniques. Data collection techniques were carried out through a questionnaire with a Likert scale. Data were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination. The results of the study indicate that partially price, store ambience, and service quality have a positive and significant effect on customer loyalty at Fritto Chicken Medan City. Simultaneously, price, store ambience, and service quality also have a positive and significant effect on customer loyalty. The service quality variable is the most dominant variable influencing customer loyalty. The results of this study are expected to be a consideration for companies in increasing customer loyalty through appropriate pricing, a comfortable restaurant atmosphere, and quality service.